Analisis Dampak Perubahan Cuaca Terhadap Keanekaragaman Hayati dalam Evolusi Biologi (Indo-MathEdu Intellectuals Journal, 2025)
Global climate change has become one of the biggest challenges to biodiversity around the world. This article explores the effects of climate change on species evolutionary pathways, focusing on the mechanisms of adaptation and speciation that occur in response to environmental change. This article highlights the importance of ecosystem conservation and management to support a sustainable evolutionary process. The type of research used is a literature study. Analysis of ecological and genetic data to analyze temperature fluctuations, changes in rainfall patterns, and increasing frequency of extreme weather events affect the habitat and resources available to the species. Our findings confirm that climate change is not only a threat to biodiversity, but also a significant driver in the evolutionary path, which can lead to new and complex ecosystem dynamics. Through a better understanding of the interactions between climate change and evolution, we can formulate more effective strategies to protect biodiversity in the future.